2010
DOI: 10.1037/a0018387
|View full text |Cite
|
Sign up to set email alerts
|

The family environment as a moderator of psychosocial outcomes following traumatic brain injury in young children.

Abstract: Objective This study sought to determine whether the family environment moderates psychosocial outcomes after traumatic brain injury (TBI) in young children. Method Participants were recruited prospectively from consecutive hospital admissions of 3-6 year old children, and included 19 with severe TBI, 56 with complicated mild/moderate TBI, and 99 with orthopedic injuries (OI). They completed four assessments across the first 18 months post-injury. The initial assessment included measures of parenting style, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
194
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(234 citation statements)
references
References 56 publications
34
194
5
1
Order By: Relevance
“…Social/behavioral outcomes were predicted by family function, in keeping with previous reports from school-age samples and evaluation more proximal to time of injury. 10,12,15 Apparently, although injury factors, such as severity and brain pathology, are relevant to early outcome, they become less important with time since injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social/behavioral outcomes were predicted by family function, in keeping with previous reports from school-age samples and evaluation more proximal to time of injury. 10,12,15 Apparently, although injury factors, such as severity and brain pathology, are relevant to early outcome, they become less important with time since injury.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Few studies, however, have prospectively followed survivors of early TBI into adolescence, and those available focus primarily on cognition. In addition, several factors have been identified that contribute to deficits after school-aged TBI (injury severity and age, premorbid child and family function), [9][10][11][12][13] but it is unclear whether these factors also explain outcomes for younger children.…”
mentioning
confidence: 99%
“…Consequently, significant differences after rehabilitation of pre-school children compared to school-aged children referring to increased social and behavioural impairment have been analysed [20,40]. In contrast to this assumption, the association of injury severity and outcome deficits diminishes with increasing time since injury [28,36,41], suggesting other influencing factors like social and family environment [37,42].…”
Section: Paediatric Tbimentioning
confidence: 98%
“…Aspects of the home environment, such as parental responsiveness, negativity, and discipline practices, are linked to a child' s behavioral recovery (Wade et al, 2011a;Wade et al, 2002). Economic and social disadvantage have been associated with poor cognitive and academic outcomes following severe TBI (Taylor et al, 2002;Yeates, Taylor, Walz, Stancin, and Wade, 2010). Well-functioning caregivers and available financial and social supports contribute to better recovery and outcomes (Sander et al, 2002;Sander et al, 2009).…”
Section: Social-environmental Factorsmentioning
confidence: 99%